Phylogenetic designation of enterovirus 71 genotypes and subgenotypes using complete genome sequences - Chan, Y.F.; Sam, I.C.; AbuBakar, Sazaly (2010)
Human enterovirus 71 (EV-71) is genotyped for molecular epidemiological investigation mainly using the two structural genes, VP1 and VP4. Based on these, EV-71 is divided into three genotypes, A, B and C, and within the genotypes B and C, there are further subgenotypes, B1-B5 and C1-C5. Classification using these genes is useful but gives incomplete phylogenetic information. In the present study, the phylogenetic relationships amongst all the known EV-71 and human enterovirus A (HEV-A) isolates with complete genome sequences were examined. A different tree topology involving EV-71 isolates of subgenotypes, C4 and B5 was obtained in comparison to that drawn using VP1. The nucleotide sequence divergence of the C4 isolates was 18.11 (17-20) when compared to other isolates of subgenotype C. However, this positions the C4 isolates within the cut-off divergence value of 17-22 used to designate the virus genotypes. Hence, it is proposed here that C4 should be designated as a new genotype D. In addition, the subgenotype B5 isolates had an average nucleotide divergence of only 6.14 (4-8) when compared to other subgenotype B4 isolates. This places the B5 isolates within the subgenotype B4. It is proposed here that the B5 isolates to be redesignated as B4. With the newly proposed genotype D and inclusion of subgenotype B5 within B4, the average nucleotide divergence between genotypes was 18.99 (17-22). Inter- and intra-subgenotype average divergences were 12.02 (10-14) and 3.92 (1-10), respectively. A phylogenetic tree built using the full genome sequences is robust as it takes into consideration changes in the sequences of both the structural and non-structural genes. Similar nucleotide similarities, however, were obtained if only VP1 and 3D RNA polymerase genes were used. Furthermore, addition of 3D RNA polymerase sequences will also show recombination events. Hence, in the absence of full genome sequences, it is proposed here that a combination of VP1 and 3D RNA polymerase gene sequences be used for initial genotyping of EV-71 isolates.